2015
DOI: 10.1002/bmc.3494
|View full text |Cite
|
Sign up to set email alerts
|

Volatile organic compounds generated by cultures of bacteria and viruses associated with respiratory infections

Abstract: Respiratory infections (RI) can be viral or bacterial in origin. In either case, the invasion of the pathogen results in production and release of various volatile organic compounds (VOCs). The present study examines the VOCs released from cultures of five viruses (influenza A, influenza B, adenovirus, respiratory syncitial virus and parainfluenza 1 virus), three bacteria (Moraxella catarrhalis, Haemophilus influenzae and Legionella pneumophila) and Mycoplasma pneumoniae isolated colonies. Our results demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 24 publications
1
50
0
Order By: Relevance
“…The factor analysis identified one factor consisting of cyclohexane, methylcyclohexane and benzaldehyde. Methylcyclohexane is found in consumer products (Sack and Steele, 1992) but can also be emitted from pathogenic bacteria associated with respiratory infections (Abd El Qader et al, 2015). In the large European AIRMEX study, the mean indoor levels of methylcyclohexane in public buildings/schools was the same as in our study (2.9 μg/m 3 ) but the outdoor levels were much lower (0.4 μg/m 3 ) (Geiss et al, 2011).…”
Section: Discussionsupporting
confidence: 55%
“…The factor analysis identified one factor consisting of cyclohexane, methylcyclohexane and benzaldehyde. Methylcyclohexane is found in consumer products (Sack and Steele, 1992) but can also be emitted from pathogenic bacteria associated with respiratory infections (Abd El Qader et al, 2015). In the large European AIRMEX study, the mean indoor levels of methylcyclohexane in public buildings/schools was the same as in our study (2.9 μg/m 3 ) but the outdoor levels were much lower (0.4 μg/m 3 ) (Geiss et al, 2011).…”
Section: Discussionsupporting
confidence: 55%
“…Aksenov et al ( 8 ) determined that VOC produced by B lymphoblastoid cells following infection with three live influenza virus subtypes were unique for each virus subtype. In addition, Abd El Qader et al ( 9 ) examined the VOC released from cultures of five viruses (influenza A, influenza B, adenovirus, respiratory syncitial virus, and parainfluenza 1 virus) and four bacteria ( Moraxella catarrhalis , Haemophilus influenza , Legionella pneumophila , and Mycoplasma pneumoniae ). The researchers detected 12 and 6 VOC that were associated with bacterial and viral growth and identified 2 VOC that were differentiated between bacterial and viral infection ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Abd El Qader et al ( 9 ) examined the VOC released from cultures of five viruses (influenza A, influenza B, adenovirus, respiratory syncitial virus, and parainfluenza 1 virus) and four bacteria ( Moraxella catarrhalis , Haemophilus influenza , Legionella pneumophila , and Mycoplasma pneumoniae ). The researchers detected 12 and 6 VOC that were associated with bacterial and viral growth and identified 2 VOC that were differentiated between bacterial and viral infection ( 9 ). Lastly, Mashir et al ( 10 ) administered live attenuated H1N1 vaccine (FluMist ® ) to humans and demonstrated that exhaled breath VOC increased for 7 days after the vaccination.…”
Section: Introductionmentioning
confidence: 99%
“…The human body produces volatile organic compounds (VOCs) either physiologically or pathologically [7][8][9]. The identification of VOCs associated with specific pathological states and their use as potential biomarkers [10] is highly complex.…”
Section: Introductionmentioning
confidence: 99%